THE EFFECT OF MOTOR VEHICLE TAXPAYER KNOWLEDGE, TAX PAYMENT SYSTEM (E-SAMSAT) AND TAXPAYER AWARENESS ON MOTOR VEHICLE TAXPAYER COMPLIANCE IN THE CITY OF BANDUNG - Fauziah, Yulistia Resti; Ginting, Wajib (Universitas Indonesia Membangun, 2022)
This study aims to find out how the Effect of Tax Knowledge, Tax Sanctions and Taxpayer Awareness on Taxpayer Compliance in Paying Land and Building Taxes in Cimaung District, Bandung Regency. The method in this study is a quantitative method through a descriptive and verification approach. The population in this study were registered taxpayers in Cimaung District, Bandung Regency, amounting to 29,090 registered SPPT and using a random sample of 100 respondents obtained using the slovin formula. Data analysis in this study used descriptive analysis, classical assumption test, multiple linear regression test, correlation coefficient test, coefficient of determination test and hypothesis testing either partially (t test) or simultaneously (F test). Data processing using SPSS version 26.0 application. The results showed that in testing the hypothesis (t test), that Tax Knowledge had no effect on Taxpayer Compliance. significance > 0.05. Tax sanctions partially have a significant effect on taxpayer compliance with a regression coefficient of 3.093 > 1.985 and a significance value of 0.003 which indicates that the significance level is <0.05. Taxpayer awareness partially has a significant effect on taxpayer compliance with a regression coefficient of 3.509 > 1.985 and a significance value of 0.001 which indicates that the significance level is < 0.05.